2018
DOI: 10.1039/c8cp01316k
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the role of W doping in BiVO4 photoanodes used for solar water splitting

Abstract: n-Type doping has been widely employed to enhance the performance of a photoanode in a photoelectrochemical cell used for water splitting. However, little is known about how doping affects the catalytic activity during surface catalysis. Herein, we took BiVO4 as an example to investigate the effect of doping on surface catalysis from both experimental and theoretical perspectives. To enable an impartial comparison, we have prepared planar BiVO4 thin films with and without W doping. It was found that W doping h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 36 publications
0
30
0
1
Order By: Relevance
“…BiVO 4 is usually used after doping with a higher valence metal ion (than V), such as Mo or W, to improve its electron conduction and charge separation (Zhao et al., 2018a, Zhao et al., 2018b). In this work, we adopted n-type doping by 3 at% Mo, which enhances the photocurrent density (Luo et al., 2011).…”
Section: Resultsmentioning
confidence: 99%
“…BiVO 4 is usually used after doping with a higher valence metal ion (than V), such as Mo or W, to improve its electron conduction and charge separation (Zhao et al., 2018a, Zhao et al., 2018b). In this work, we adopted n-type doping by 3 at% Mo, which enhances the photocurrent density (Luo et al., 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a Ti 3d defect state in the band gap of titania also plays an important role in the surface catalysis of defect contained TiO2 [86]. Zhao et al also revealed that W doping and W-Ti codoping into BiVO4 have led to more active sites on the surface and reduced charge transfer resistance (Figure 23) [87,88]. Theoretical calculation revealed that Ti sites become active after the codoping.…”
Section: Active Sitesmentioning
confidence: 98%
“…如何降低载流子复合、优化界面能级匹 配以及减小过电位和能量损失是BiVO 4 光阳极发展的 重要方向 [22,23] . 近年来, 这些方面有了很大的进展, 如 通过陷光结构或碳量子点(carbon quantum dots, CQDs) 增强BiVO 4 吸光能力与光响应范围从而增加其J max 或 LHE [21,24] ; 通过缺陷态的引入与异质结的构建从而增 强其Φ Sep [25,26] ; 通过引入助催化剂或对电极表面处理从 而增强Φ OX [27,28] .…”
Section: 因氢能具有环境友好、热值高、无毒等优势 太阳能unclassified